CAPABILITIES OF NATURAL REMEDIES IN SYMPTOMATIC TREATMENT AND PROPHYLAXIS OF PEDIATRIC INFLAMMATORY DISEASES OF THE PHARYNX - E.Yu. Radzig; N.V. Ermilova; M.R. Bogomilskiy; E.A. Tsarevskaya ("Paediatrician" Publishers LLC, 2011)
The article is dedicated to the problem of effective diagnostics and treatment of acute pharyngitis. Authors discuss problems of etiopathogenesis and treatment. What is being stressed in the article - it's the capability of natural remedy in treatment and prophylaxis of inflammatory pathology of the pharynx in children, including those from welfare institutions. Key words: acute pharyngitis, natural remedy, seasonal increase in acute respiratory infection prophylaxis, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 88-92.)